2019
DOI: 10.1002/nop2.341
|View full text |Cite
|
Sign up to set email alerts
|

Challenges and facilitators of professional socialization: A systematic review

Abstract: AimsThis current study aimed to present a review of the challenges and facilitators of professional socialization among undergraduate nursing students.DesignSystematic review.MethodsA literature search was conducted in Embase, Google Scholar, PubMed and Scopus in April and May 2018 for studies published in the English language. Four thousand three hundred fifty‐two articles were retrieved. We conducted further screening for full‐text articles after discarding duplicates and irrelevant studies. Finally, eight s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
49
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(50 citation statements)
references
References 35 publications
1
49
0
Order By: Relevance
“…Being cyclical means that by increasing one's competency, one obtains more selfconfidence and improves one's capabilities through a self-reinforcing process (24). Professional socialization is a lifelong process (28,41,42) and does not stop when the period of formal education ends. According to the interactionism theory, the process of professional socialization can be considered as a role-taking process, which requires a continuous modification of one's role, as one enters different working environments with different facilities and challenges (43).…”
Section: The Most Important Features Of the Professional Socializatiomentioning
confidence: 99%
“…Being cyclical means that by increasing one's competency, one obtains more selfconfidence and improves one's capabilities through a self-reinforcing process (24). Professional socialization is a lifelong process (28,41,42) and does not stop when the period of formal education ends. According to the interactionism theory, the process of professional socialization can be considered as a role-taking process, which requires a continuous modification of one's role, as one enters different working environments with different facilities and challenges (43).…”
Section: The Most Important Features Of the Professional Socializatiomentioning
confidence: 99%
“…However, the researchers pointed to the facilitators of professional socialization, such as professional context (Dinmohammadi et al 2017), supportive teachers (Curtis et al 2012), and interactive learning (Holley and Taylor 2009). Research has also confirmed that studies with small samples of interviews are suitable for exploring deep structures and interpersonal problems (Salisu et al 2019).…”
Section: Professional Socialization Of Trainees In Helping Professionsmentioning
confidence: 90%
“…As in the meta-analysis of the literature by Barretti (2004a), Salisu et al (2019) conducted a systematic review of facilitators and challenges of professional socialization, and a narrative synthesis was used to analyze the available data. They found that eight studies pointed to such challenges of professional socialization, such as incongruence of theory and practice (Zarshenas et al 2014), disintegration (Dinmohammadi et al 2017), and focused education (Condon and Sharts-Hopko 2010).…”
Section: Professional Socialization Of Trainees In Helping Professionsmentioning
confidence: 99%
“…Dinmohammadi et al conducted a concept analysis of nursing professional socialization and found that professional socialization is a complex process with four key attributes: learning, interaction, development, and adaptation [5]. Salisu et al stated that the attributes and antecedents of professional identity of the nurse are related to the personal dimensions of competence, con dence, insight, capability, and selfre ection ability [2]. Nursing competency also has an in uence on professional socialization [1,5,6,18].…”
Section: Professional Socialized and Nursing Competencementioning
confidence: 99%
“…The objectives of this study are as follows: (1) To verify the reliability and validity of the professional socialization model as a means to study the key aspects of self-learning effectiveness, caring behavior, self-re ection, and nursing competence. (2) To determine whether there are differences in the effects of the professional socialization model in terms of gender. In order to achieve the above research purposes, we perform the following literature review.…”
Section: Introductionmentioning
confidence: 99%